Pet owners' perceptions of veterinary safety practices. (17th November 2018) - Fowler, Heather; Irimia, Bianca; Ramirez, Vickie; Meischke, Hendrika; Rabinowitz, Peter
Abstract : Veterinary workers must care for their animal patients while simultaneously protecting their own health and safety. This process can be complicated by the presence and perception of pet owners who may not agree with a given tactic used to protect veterinary workers from injury. We conducted focus groups of pet owners in the Seattle area during November 2016 to gain a deeper understanding of their perceptions relating to veterinary worker safety practices. Focus group interviews were recorded and transcribed and study themes identified and summarised. Twenty pet owners participated in three focus groups. Study themes arising from the focus group discussions could be categorised into human, animal, behavioural and environmental domains as outlined in a One Health Occupational Safety and Health (OHOSH) model. Communication was a recurring study theme identified, suggesting that lacking or impaired veterinary personnel‐client communication plays a key role in the safe delivery of veterinary services and can negatively impact the use of safety practices among veterinary personnel. Our study suggests that it is important for veterinary personnel to communicate to clients the reasons for policies related to worker safety. Such communication can help engage the veterinary client in order to effectively avoid situations that precipitate injury.